Stop Out Dashboard Understanding Attrition Among New Freshmen & Transfers
Each Fall the Stop Out Survey is administered to students who were new freshmen or new transfers the previous year butdid not return for their second fall semester. As the visualizations below demonstrate, this dashboard explores both theresults of the stop out survey as well as information on all new students who stop out before their second year.